Age-specific patterns of DBLα var diversity can explain why residents of high malaria transmission areas remain susceptible to Plasmodium falciparum blood stage infection throughout life. Issue 11 (October 2022) - Ruybal-Pesántez, Shazia; Tiedje, Kathryn E.; Pilosof, Shai; Tonkin-Hill, Gerry; He, Qixin; Rask, Thomas S.; Amenga-Etego, Lucas; Oduro, Abraham R.; Koram, Kwadwo A.; Pascual, Mercedes; Day, Karen P.
Graphical abstract: Highlights: Age-specific Plasmodium falciparum var diversity patterns were measured in a cohort of 1, 541 individuals in Ghana. We define 42, 399 distinct var sequence variants organised as non-overlapping repertoires within individuals. Risk of infection with parasites with diverse var repertoires exists at any age. High seasonal turnover of parasites with diverse isolate var repertoires was also observed in individuals of all ages. Simulations illustrate why adolescents and adults remain susceptible to blood stage infection, even with multiple genomes. Abstract: Immunity to Plasmodium falciparum is non-sterilising, thus individuals residing in malaria-endemic areas are at risk of infection throughout their lifetime. Here we seek to find a genomic epidemiological explanation for why residents of all ages harbour blood stage infections despite lifelong exposure to P. falciparum in areas of high transmission. We do this by exploring, for the first known time, the age-specific patterns of diversity of variant antigen encoding ( var ) genes in the reservoir of infection. Microscopic and submicroscopic P. falciparum infections were analysed at the end of the wet and dry seasons in 2012–2013 for a cohort of 1541 residents aged from 1 to 91 years in an area characterised by high seasonal malaria transmission in Ghana. By sequencing the near ubiquitous Duffy-binding-like alpha domain (DBLα) that encodes immunogenic domains, we defined var gene diversity in an estimated 1096 genomes detected in sequential wet and dry season sampling of this cohort. Unprecedented var (DBLα) diversity was observed in all ages with 42, 399 unique var types detected. There was a high degree of maintenance of types between seasons (>40% seen more than once), with many of the same types, especially upsA, appearing multiple times in isolates from different individuals. Children and adolescents were found to be significant reservoirs of var DBLα diversity compared with adults. Var repertoires within individuals were highly variable, with children having more related var repertoires compared to adolescents and adults. Individuals of all ages harboured multiple genomes with var repertoires unrelated to those infecting other hosts. High turnover of parasites with diverse isolate var repertoires was also observed in all ages. These age-specific patterns are best explained by variant-specific immune selection. The observed level of var diversity for the population was then used to simulate the development of variant-specific immunity to the diverse var types under conservative assumptions. Simulations showed that the extent of observed var diversity with limited repertoire relatedness was sufficient to explain why adolescents and adults in this community remain susceptible to blood stage infection, even with multiple genomes.